An analytic homogenization model in traction and bending for orthotropic composite plates with the type of double corrugated cardboard - Minh, Duong Pham Tuong; Khoa, Ngo Nhu (Vietnam Journal of Mechanics, 2016)
In this paper, an analytic homogenization model in traction and flexion for the double corrugated cardboard plates is presented. The proposed analytical homogenization model allows modelling the 3D double corrugated cardboard with a 2D homogenized plate. This model is essentially based on the theory of stratification and then improved by using the theory of sandwich. This model was validated by comparing the results of Abaqus-3D and H-2D model using "user’s subroutine" "UGENS". The homogenization model can be used not only for corrugated cardboard plates, but also for naval and aeronautic composite structures.